Effects of Different TiO2 Particle Sizes on the Microstructure and Optical Limiting Properties of TiO2/Reduced Graphene Oxide Nanocomposites - Yuyu Ren; Lili Zhao; Yang Zou; Lixin Song; Ningning Dong; Jun Wang (Nanomaterials, 2019)
TiO2/reduced graphene oxide (rGO) nanocomposites with two different TiO2 particle sizes were synthesized by a facile hydrothermal method using two different source materials of Ti: tetrabutyl titanate (TBT) and commercial TiO2 powder (P25). For respective series with the same source materials, we investigated additions that optimized the nonlinear optical properties (NLO) and optical limiting (OL) performances, and we explored the relationships between structural diversity and performance. Several characterization techniques, including X-ray powder diffraction (XRD), X-ray photoelectron spectroscopy (XPS), transmission electron microscopy (TEM), Fourier-transform infrared spectroscopy (FTIR), Raman spectroscopy, and diffuse reflectance ultraviolet-visible spectroscopy (UV-Vis) were conducted to confirm the microstructures and chemical states of as-prepared materials. This indicated the existence of the Ti–O–C bond between rGO sheets and TiO2 particles and the reduction from precursor graphene oxide (GO) to rGO. The results of UV-Vis spectra revealed that the TiO2/rGO nanocomposites showed smaller band gaps than bare TiO2. A nanosecond open-aperture Z-scan technique at 1064 nm was applied to investigate NLO and OL properties. TiO2/rGO nanocomposites exhibited enhanced NLO and OL performances, arising from synergistic effects, compared to individual components. The TBT series samples performed better than the P25 series, presumably relevant to dimensional effects.